A study on the factors that influence level of awareness of UiTM KBM students towards ‘no plastic bag campaign’ / Farah Syazwani Jailani and Norfarhana Ismail - Jailani, Farah Syazwani; Ismail, Norfarhana (Faculty of Administrative Science and Policy Studies, 2013)
The purpose of this research is to analyse the factor that influence level of awareness of UiTM KBM students towards ‘No Plastic Bag Campaign’. The research discussed three factors that influence the level of awareness which are environmental knowledge, behaviour and role of mass media. The approach of this research were tested using the spearman-rank order correlation. Data were collected among 200 of students in UiTM Kampus Bandaraya Melaka. The implication of this study is that environmental knowledge, behaviour and role of mass media can influence the level of awareness of students at UiTM Kampus Bandaraya Melaka.